Dampak Restitusi Terhadap Kesehatan Mental Anak Korban Persetubuhan: Studi Longitudinal - Atika Sari; Nandang Sambas (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to analyze the impact of restitution on the mental health of child victims of sexual intercourse from a long-term perspective through a longitudinal approach. The main focus of this research is to evaluate the effectiveness of restitution as a form of legal protection and psychological recovery for child victims of sexual crimes. The contribution of this study lies in reinforcing the argument that restitution is not merely financial compensation but also a crucial instrument in trauma recovery and the restoration of safety and self-worth in child victims. This research employs a juridical-empirical approach with a longitudinal method, combining normative analysis of restitution regulations with observation and interviews involving child victims who received restitution over a specific period. The findings conclude that restitution in criminal law functions as a form of recovery that is not limited to financial aspects but also serves as recognition of the victim’s suffering and as a component of restorative justice. This longitudinal study demonstrates that comprehensive restitution, supported by psychosocial interventions, has a positive impact on the mental health recovery of child victims of sexual abuse.